DNMT1 methylation of LncRNA-ANRIL causes myocardial fibrosis pyroptosis by interfering with the NLRP3/Caspase-1 pathway: DNMT1 methylation of ANRIL in myocardial fibrosis - Liu, Zuntao; Gao, Lei; Kan, Chenjing; Chen, Xin; Shi, Kaihu; Wang, Wei (Cellular and Molecular Biology, 2024)
Myocardial fibrosis is a common pathological manifestation that occurs in various cardiac diseases. The present investigation aims to reveal how DNMT1/lncRNA-ANRIL/NLRP3 influences fibrosis and cardiac fibroblast pyroptosis. Here, we used ISO to induce myocardial fibrosis in mice, and LPS and ATP to induce myocardial fibroblast pyroptosis. The results showed that DNMT1, Caspase-1, and NLRP3 expression were significantly increased in fibrotic murine myocardium and pyroptotic cardiac fibroblasts, whereas LncRNA-ANRIL expression was decreased. DNMT1 overexpression decreased the level of LncRNA-ANRIL while increasing the levels of NLRP3 and Caspase-1. Contrarily, silencing DNMT1 increased the LncRNA-ANRIL and decreased the levels of NLRP3 and Caspase-1. Silencing LncRNA-ANRIL increased the levels of NLRP3 and Caspase-1. The present findings suggest that DNMT1 can methylate LncRNA-ANRIL during the development of myocardial fibrosis and CFs cell scorching, resulting in low LncRNA-ANRIL expression, thereby influencing myocardial fibrosis and cardiac fibroblast pyroptosis.